Bijective Product and Product Square k-Cordial Labeling of Graphs - Shiu, W.C.; Sabibha, R. Santrin; Jeyanthi, P.; Jeya Daisy, K.; Lau, G.C. (Jordan Journal of Mathematics and Statistics, 2024)
In this paper, we introduce two new concepts namely bijective product k-cordial labeling and bijective product square kcordial labeling and show that some standard graphs admit bijective product k-cordial labeling, where k = 2, 3. Also, we establish that the path, cycle, flower, helm and gear graphs are bijective product square 3-cordial graphs.